PRE-SEQUENCES AND SPEECH ACTS IN CEBUANO RADIO HEALTH COMMERCIALS IN CEBU CITY - Apalla, Ceska Marie R; San Juan, Keeshia Joy S; Maxilom, Rowanne Marie R (Kajian Linguistik dan Sastra, 2017)
This research attempted to identify and analyze the Cebuano-Bisaya radio health commercials using Schegloffâs (2007) framework on pre-sequences with the support of Yuleâs (1996) speech act theory. Thirty (30) Cebuano-Bisaya radio health commercials were gathered from two selected radio stations. The results revealed that representatives were the most dominant function in speech acts that reflected in pre-sequences specifically with pre-offers and pre-announcements throughÂ  dramaÂ  andÂ  testimonialÂ  categoriesÂ  whichÂ  areÂ  oftenÂ  usedÂ  inÂ  medicinal productÂ  commercials.Â  InÂ  advertisingÂ  strategies,Â  Cebuano-BisayaÂ  commercials useÂ  RepresentativesÂ  andÂ  ExpressiveÂ  asÂ  persuasiveÂ  devicesÂ  inÂ  addressingÂ  the advertisersâ intendedÂ  messageÂ  toÂ  theÂ  targetÂ  audience.Â  Also,Â  Cebuano-Bisaya commercials used Representatives and Expressive as an appeal to suggest an intention for the listener to buy advertised products.Keywords: Cebuano, commercial, health, pre-sequences, radio, speech acts